And the band played on [videorecording (DVD)] - Spottiswoode, Roger; Modine, Matthew; Alda, Alan, 1936-; Collins, Phil; Gere, Richard, 1949-; Huston, Anjelica; Shilts, Randy (HBO Home Video, 2010)
Follows the struggle of a handful of strong-willed men and women who took on the fight to save lives in the face of a mysterious illness now called AIDS.